2014
DOI: 10.1002/ar.22983
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mechanotransduction on Vascular Smooth Muscle Myocytes Cytoskeleton and Contractile Function

Abstract: Smooth muscle exhibits a highly organized structural hierarchy that extends over multiple spatial scales to perform a wide range of functions at the cellular, tissue, and organ levels. Early efforts primarily focused on understanding vascular smooth muscle function through biochemical signaling. However, accumulating evidence suggests that mechanotransduction, the process through which cells convert mechanical stimuli into biochemical cues, is requisite for regulating contractility. Cytoskeletal proteins that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 133 publications
0
29
0
Order By: Relevance
“…When smooth muscle cells contract, they can both shorten and increase their stiffnesses [25,26] through actomyosin contractility and through rearrangements of the cytoskeleton, for example, by repolymerizing actin [27]. The stiffness of a smooth muscle cell arises from its contractile network of actin fibres and myosin, along with its intermediate filament cytoskeleton of vimentin and desmin [28][29][30][31] (figure 1). Atomic force microscopy (AFM) studies on relaxed, dissected embryonic chicken gut sections have found that the muscular layer has a lower stiffness than the epithelium [32,33], but after contractile stimulation, individual smooth muscle cells can become at least twice as stiff as epithelial cells, even when muscle cells are prevented from physically shortening [34,35].…”
Section: Definition and Properties Of Smooth Musclementioning
confidence: 99%
“…When smooth muscle cells contract, they can both shorten and increase their stiffnesses [25,26] through actomyosin contractility and through rearrangements of the cytoskeleton, for example, by repolymerizing actin [27]. The stiffness of a smooth muscle cell arises from its contractile network of actin fibres and myosin, along with its intermediate filament cytoskeleton of vimentin and desmin [28][29][30][31] (figure 1). Atomic force microscopy (AFM) studies on relaxed, dissected embryonic chicken gut sections have found that the muscular layer has a lower stiffness than the epithelium [32,33], but after contractile stimulation, individual smooth muscle cells can become at least twice as stiff as epithelial cells, even when muscle cells are prevented from physically shortening [34,35].…”
Section: Definition and Properties Of Smooth Musclementioning
confidence: 99%
“…Contraction of the SMCs can influence blood flow in small arteries but does not play this role in aorta. 15, 16 Rather, SMC contraction may function as a mechanosensor in the aorta.…”
Section: Smooth Muscle Cell Contractile Unit and Mechanotransductionmentioning
confidence: 99%
“…The dilatation of the ECM under SMC contraction is due to cell-generated forces pulling on the fibres of the ECM: contractile elements within SMCs are known to be mechanically connected to extracellular fibres (e.g. collagen) through integrins (Moiseeva, 2001, Ye et al, 2014, Bursa et al, 2011), causing a widening of intercellular channels as seen in Fig. 5 and increasing the strain in the matrix.…”
Section: Discussionmentioning
confidence: 99%